Noninvasive respiratory support after extubation: a systematic review and network meta-analysis - Annalisa Boscolo; Tommaso Pettenuzzo; Nicolò Sella; Matteo Zatta; Michele Salvagno; Martina Tassone; Chiara Pretto; Arianna Peralta; Luisa Muraro; Francesco Zarantonello; Andrea Bruni; Federico Geraldini; et al. (European Respiratory Review, 2023)
Background The effect of noninvasive respiratory support (NRS), including high-flow nasal oxygen, bi-level positive airway pressure and continuous positive airway pressure (noninvasive ventilation (NIV)), for preventing and treating post-extubation respiratory failure is still unclear. Our objective was to assess the effects of NRS on post-extubation respiratory failure, defined as re-intubation secondary to post-extubation respiratory failure (primary outcome). Secondary outcomes included the incidence of ventilator-associated pneumonia (VAP), discomfort, intensive care unit (ICU) and hospital mortality, ICU and hospital length of stay (LOS), and time to re-intubation. Subgroup analyses considered “prophylactic” versus “therapeutic” NRS application and subpopulations (high-risk, low-risk, post-surgical and hypoxaemic patients). Methods We undertook a systematic review and network meta-analysis (Research Registry: reviewregistry1435). PubMed, Embase, CENTRAL, Scopus and Web of Science were searched (from inception until 22 June 2022). Randomised controlled trials (RCTs) investigating the use of NRS after extubation in ICU adult patients were included. Results 32 RCTs entered the quantitative analysis (5063 patients). Compared with conventional oxygen therapy, NRS overall reduced re-intubations and VAP (moderate certainty). NIV decreased hospital mortality (moderate certainty), and hospital and ICU LOS (low and very low certainty, respectively), and increased discomfort (moderate certainty). Prophylactic NRS did not prevent extubation failure in low-risk or hypoxaemic patients. Conclusion Prophylactic NRS may reduce the rate of post-extubation respiratory failure in ICU patients.